Pengembangan LKPD Berbasis Model Pembelajaran Kooperatif Tipe Think Talk Write Pada Pembelajaran Matematika - Putri Dwi Hardini; Murni Sulistyaningsih; Vivian E. Regar (Departement of Mathematics Education, 2023)
Putri Dwi Hardini. 19504114. Development Learning Based of LKPD on the Cooperative Model Think Talk Write Type in Mathematics Learning. Mathematics Department. Faculty of Mathematics, Natural and Earth Sciences. Manado State University. Tondano. 2023. This research is motivated by problems found in learning mathematics which are found from various aspects, one of which is the lack of proper use of Student Worksheets (LKPD). The purpose of this study was to produce Student Worksheets (LKPD) on Triangle material with the Think Talk Write (TTW) type cooperative learning model in class VII SMP Negeri 7 Kotamobagu which is valid, practical and effective. This type of research is research and development (R&D) using the 4-D development model (define, design, develop, and disseminate). The assesment score from the results of the expert validator’s assessment is 95 with a very valid category. For the practicality assessment score seen from the teacher’s response with a score of 98 and for student responses with a score of 87 in the very good category. The develop LKPD meets the effective criteria based on a classical learning completeness percentage of 79%. In conclusion, the developed LKPD is valid, pratical, effective for use in learning.